High prevalence of asymptomatic cervical spine subluxation in patients with rheumatoid arthritis waiting for orthopaedic surgery. Issue 7 (3rd November 2005) - Neva, M H; Häkkinen, A; Mäkinen, H; Hannonen, P; Kauppi, M; Sokka, T
Abstract : Objective: To study the prevalence of cervical spine subluxation in patients with rheumatoid arthritis waiting for orthopaedic surgery, and symptoms that might be associated with the disorders. Methods: 194 patients with rheumatoid arthritis were referred for orthopaedic surgery at Jyväskylä Central Hospital, 154 (79%) of whom volunteered for the present study including clinical examination, laboratory tests, radiographs of the cervical spine, hands, and feet, and self report questionnaires. Definition of anterior atlantoaxial subluxation (aAAS) was >3 mm and of subaxial subluxation (SAS) ⩾3 mm. Atlantoaxial impaction (AAI) was analysed following to the Sakaguchi-Kauppi method. Results: 67 patients (44%) had cervical spine subluxation or previous surgical fusion. The prevalence of aAAS, AAI, SAS, or previous fusion was 27 (18%), 24 (16%), 29 (19%), and 8 (5%), respectively; 69% of patients with cervical spine subluxations (those with fusions excluded) reported neck pain, compared with 65% of patients without subluxations (p = 0.71). The prevalence of occipital, temporal, retro-orbital, and radicular pain in upper extremities was similar in patients with or without cervical spine subluxations (54% v 43%; 17% v 31%; 25% v 24%; 47% v 48%, respectively). However, patients with subluxations were older, had longer disease duration, more active disease, poorer function according to the Health Assessment Questionnaire, and had more often erosive disease. Conclusions: Asymptomatic cervical spine subluxation is common in patients with rheumatoid arthritis waiting for orthopaedic surgery. Regardless of symptoms, the possibility of cervical spine subluxation in patients with severe rheumatoid arthritis should be considered in preoperative evaluation.